2019
DOI: 10.4314/jasem.v22i12.14
|View full text |Cite
|
Sign up to set email alerts
|

Total petroleum hydrocarbon content in surface water and sediment of Qua-Iboe River, Ibeno, Akwa-Ibom State, Nigeria

Abstract: The total petroleum hydrocarbon content in surface water and sediment of Qua Iboe River, Akwa Ibom State, Nigeria was assessed by randomly collecting samples from five sampling points of the study area and from a control site. The samples were extracted with dichloromethane (DCM) by liquid-liquid partition for water and Soxhlet extraction for sediments followed by subsequent clean up on column chromatography and analyzed by gas chromatography-flame ionization detection (GC-FID) for the determination of total p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…They are important environmental pollutants that pose threat to human health particularly marine environment if not handled properly. The values are significantly lower than the recommended values [31][32][33][34].…”
Section: Resultsmentioning
confidence: 63%
“…They are important environmental pollutants that pose threat to human health particularly marine environment if not handled properly. The values are significantly lower than the recommended values [31][32][33][34].…”
Section: Resultsmentioning
confidence: 63%
“…The level of contamination by total petroleum hydrocarbon in the sediment of Taylor Creek are shown in Tables 1 to 4. Most river pollutants found themselves at the bottom part of the river and therefore the bottom (sediment) is the residue or sink for pollutants in the rivers of the Niger Delta region of Nigeria and elsewhere in the world (Inyang et al, 2018). Table 1 showed the levels of contamination for the month of December, Table 2, for February, Table 3 for April and Table 4 for June.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that the increased count of petroleum degrading bacteria is due to the large amounts of chemicals and pollutant hydrocarbons disposed into the creeks. Inyang et al (2018) evaluated the amount of hydrocarbon in surface water and sediments at Ibeno, Nigeria. A random sampling at five different points was done and analysed by gas chromatography (GC-FID) technique.…”
Section: Evaluation Of Recent Research Effortsmentioning
confidence: 99%
“…Most of the pollution problems are located in the Niger delta region of Nigeria where most of the oil facilities are located (Aghalino and Eyinla, 2009). In previous assessments, the presence of pollutants such as oil, grease, hydrocarbons and heavy metals have been established in surface water and also in groundwater in some cities in Nigeria such as Ibadan (Adewuyi and Olowu, 2012), Warri (Aremu et al, 2002;Adewuyi et al, 2011), Port Harcourt (Ayotamuno et al, 2006;Amala, 2018), Oghara (Akporido, 2018), Ibeno (Inyang et al, 2018), Benin (Owamah, 2013), Bight of Bonny (Williams, 2007), Ogoni (Happy, 2018) and a host of other southern cities. All these pollutants have their origin from the processes involved in producing, refining and distributing petroleum and its products and by-products in Nigeria.…”
Section: Introductionmentioning
confidence: 99%